DNA methylation and transcriptional trajectories during human development and reprogramming of isogenic pluripotent stem cells. Issue 1 (December 2017) - Roost, Matthias; Slieker, Roderick; Bialecka, Monika; Iperen, Liesbeth; Gomes Fernandes, Maria; He, Nannan; Suchiman, H. Eka D.; Szuhai, Karoly; Carlotti, Françoise; Koning, Eelco; Mummery, Christine; Heijmans, Bastiaan; et al.
Abstract Determining cell identity and maturation status of differentiated pluripotent stem cells (PSCs) requires knowledge of the transcriptional and epigenetic trajectory of organs during development. Here, we generate a transcriptional and DNA methylation atlas covering 21 organs during human fetal development. Analysis of multiple isogenic organ sets shows that organ-specific DNA methylation patterns are highly dynamic between week 9 (W9) and W22 of gestation. We investigate the impact of reprogramming on organ-specific DNA methylation by generating human induced pluripotent stem cell (hiPSC) lines from six isogenic organs. All isogenic hiPSCs acquire DNA methylation patterns comparable to existing hPSCs. However, hiPSCs derived from fetal brain retain brain-specific DNA methylation marks that seem sufficient to confer higher propensity to differentiate to neural derivatives. This systematic analysis of human fetal organs during development and associated isogenic hiPSC lines provides insights in the role of DNA methylation in lineage commitment and epigenetic reprogramming in humans. While DNA methylation and gene expression data are widely available for animal models, comprehensive data from human development is rarer. Here, the authors generated transcriptional and DNA methylation data from 21 organs during human development and 6 isogenic induced pluripotent stem cell lines.